The Use of Cooperative Method Type Student Teams Achievement Division as an Effort to Increase Student Learning Outcomes in Fiqh Subjects at the Integrated Madani Islamic Elementary School in Aceh Tenggara - Harli Harli (Pusdikra Publishing, 2022)
This study aims to determine student learning outcomes in the subject of Fiqh before and after using the Student Teams Achievement Division learning model and to determine the effectiveness of students in class during learning. This study uses the type of Classroom Action Research (CAR) with II cycles and each cycle consists of planning, implementing, observing, and reflecting through the application of the Student Teams Achievement Division learning model in the Fiqh subject on Freedom of Organization. Based on the research results, it can be concluded that student learning outcomes before the action only get an average score of 64.41 or 21% success rate. After the application of the Student Teams Achievement Division learning model in cycle I, students Fiqh learning outcomes had an average score of 70.52 or 52.6% student success rate. In cycle II, an average score of 83.16 or 83.21% was obtained for the success rate of the students. This Classroom Action Research can be said to increase by using the Student Teams Achievement Division learning model.